The effect of variable arterial transducer level on the accuracy of pulse contour waveform-derived measurements in critically ill patients. - He, Huai-wu; Liu, Da-wei; Long, Yun; Wang, Xiao-ting; Zhao, Mei-ling; Lai, Xiao-li (Journal of Clinical Monitoring & Computing, 2016)
We know that a 10 cm departure from the reference level of pressure transducer position is equal to a 7.5 mmHg change of invasive hemodynamic pressure monitoring in a fluid-filled system. However, the relationship between the site level of a variable arterial pressure transducer and the pulse contour-derived parameters has yet to be established in critically ill patients. Moreover, the related quantitative analysis has never been investigated. Forty-two critically ill patients requiring PiCCO-Plus cardiac output monitoring were prospectively studied. The phlebostatic axis was defined as the zero reference level; the arterial pressure transducer was then vertically adjusted to different positions (+5, +10, +15, +20, -20, -15, -10, -5 cm) of departure from the zero reference site. The pulse contour waveform-derived parameters were recorded at each position. Elevation of the pressure transducer caused significantly positive changes in the continuous cardiac index (+CCI), stroke volume index (+SVI), and stroke volume variation (+SVV), and negative changes in the rate of left ventricular pressure rise during systole (-dP/dtmax), the systemic vascular resistance index (-SVRI), and vice versa. At the 5 cm position, the SVRI changes reached statistical significance with error. At the 10 cm position, the changes in CCI and dP/dtmax reached statistical significance with error, while the change in SVV reached statistical significance at 15 cm. The change rate of CCI was more than 5 % at the 15 cm position and approximately 10 % at the 20 cm position. On average, for every centimeter change of the transducer, there was a corresponding 0.014 L/min/m(2) CCI change and 0.36 % change rate, a 1.41 mmHg/s dP/dtmax change and 0.13 % change rate, and a 25 dyne/s/cm(5) SVRI change and 1.2 % change rate. The variation of arterial transducer position can result in inaccurate measurement of pulse contour waveform-derived parameters, especially when the transducer's vertical distance is more than 10 cm from the phlebostatic axis. These findings have clinical implications for continuous hemodynamic monitoring.